PENGELOLAAN GUDANG LOGISTIK KEMANUSIAAN BNPB - Raden Didiet Rachmat Hidayat; Mohammad Iqbal Firdaus; Lis Lesmini (Politeknik APP Jakarta, 2017)
The right storage of logistics and equipment intends to have the correct and accurate quantity to mobilize during the disaster happens. This study investigates the warehousing management activities of the National Disaster Management Authority (BNPB) in XYZ warehouse located in North Jakarta in 2014. This study was conducted using a qualitative approach because it wanted to clearly and deeply describe the warehousing management activities in implementing the warehousing guidelines that have been assigned. The authors found that warehousing management activities carried out by the National Disaster Management Authority (BNPB) complies with the regulations of the Head of National Disaster Management Authority No. 6 of 2009 on Warehousing Guidelines.